Algorithms for planning of IP of networks with through QoS by limitations - Нагорнюк, О. С. (Problems of Informatization and Control, 2007)
Attention is concentrated on a few problems, which arise up at planning of networks with commutation of packages, which the problem of capacity, problem of capacity and motion, problem of topology, capacity and motion, belong to